2016
DOI: 10.1177/0363546515618372
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Injury Prevention Programs in Adolescent Team Sports

Abstract: Clinical practitioners (eg, orthopaedics, physical therapists) and sports practitioners (eg, strength and conditioners, coaches) can respectively recommend and implement IPPs similar to those examined to help reduce injury rates in adolescent team sports contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 44 publications
3
80
0
4
Order By: Relevance
“…Though the database used for the present study did not contain information that would help identify the source of increased anterior asymmetry on the SEBT, such as ankle dorsiflexion range of motion or lower extremity muscle strength imbalances, previous research suggests that deficits in strength, flexibility, and neuromuscular control may influence injury risk. 14,18,26 To facilitate development of screening and training programs that effectively reduce injury risk, future research should aim to determine the underlying causes of increased anterior asymmetry. Sideto-side asymmetry normalized to limb length has been previously described in healthy Division I collegiate athletes, 27 but to the authors' knowledge, the present study is the first to associate these values with injury.…”
mentioning
confidence: 99%
“…Though the database used for the present study did not contain information that would help identify the source of increased anterior asymmetry on the SEBT, such as ankle dorsiflexion range of motion or lower extremity muscle strength imbalances, previous research suggests that deficits in strength, flexibility, and neuromuscular control may influence injury risk. 14,18,26 To facilitate development of screening and training programs that effectively reduce injury risk, future research should aim to determine the underlying causes of increased anterior asymmetry. Sideto-side asymmetry normalized to limb length has been previously described in healthy Division I collegiate athletes, 27 but to the authors' knowledge, the present study is the first to associate these values with injury.…”
mentioning
confidence: 99%
“…IPPs reduce injury risk by improving neuromuscular strength, agility and limb coordination with a combination of strength, plyometric and balance exercises. A meta-analysis comprising over 100 000 athletes in the review by Soomro et al showed that IPPs reduced the risk of injury by 32% (IRR=0.68, 95% CI 0.54 to 0.84, p<0.05) 6. These data support the practice of other sports such as soccer, rugby, AFL and basketball that have implemented such programmes at community level 6–10…”
Section: Introductionmentioning
confidence: 86%
“…The perfect warm-up exercise will not only make our body to exercise state, but also improve the psychological state, increase the enthusiasm of participating in sports. [6] Improve the objective conditions of amateur sports training. The front has made certain elaboration on the relationship between sports venues, equipment and sports injuries, and to break through the venue, equipment of Amateur Sports Limited, a state, society must increase the sports infrastructure investment, such as not only to build the school playground, the purchase of equipment should be, should also increase the maintenance of investment rugged, too slippery, too much debris to clean up the site, the equipment does not meet the requirements of the timely replacement and maintenance, to ensure the use function; on the other hand, the athletes before training instructors should also carry out detailed inspection of the facilities and equipment, to ensure compliance with the movement of the corresponding standards, reduce the possibility of sports injury.…”
Section: Amateur Sports Training In How To Prevent Sports Injurymentioning
confidence: 99%